Norway's Sami Parliament - Robbins, Elizabeth Jane (Arena Publications, 2009)
There are many parallels between the role and function of the Samediggi, or Sami Parliament, and the former Australian Aboriginal and Torres Strait Islander Commission (ATSIC). However, the positive approach of the Norwegian government to a popularly elected indigenous representative body is in contrast to the experience in Australia, where ATSIC was frequently at loggerheads with government, especially in the last few years of its existence.